Training In Aquatic Rescue As A Social Responsibility In A University Institution In Medellín (The Review of Diabetic Studies, 2025)
Within the framework of the Sustainable Development Goals (SDGs), this research addresses the need to strengthen training in aquatic rescue as a preventive and educational strategy. The study focused on the design and implementation of a comprehensive program aimed at the development of technical, physical and emotional competencies for emergency care in aquatic spaces, with the purpose of promoting an institutional culture of self-care and social responsibility.The methodology adopted was mixed, incorporating quantitative and qualitative tools. Theoretical, physical and psychological tests were applied before and after the training process, structured in 40% theoretical content and 60% practical. The sample was made up of people with little previous experience, which allowed us to assess the impact of the program from a training perspective.The results revealed a mean theoretical performance (average: 2.69/5), with strengths in protocols such as PRICE (93.75% of correct answers), but weaknesses in resuscitation techniques (93.75% of errors in chest compressions). In physical condition, 56.25% were between "low" and "acceptable" levels in cardiorespiratory tests, and only 25% showed optimal aptitude in the aquatic environment. In the psychological component, 62.5% had a medium level in the state of anxiety, and 37.5% at a high level.It is concluded that the training had a positive impact on the comprehensive preparation of the participants, highlighting its value as a transformative pedagogical practice, with the potential to be integrated into educational contexts that seek to promote safe environments and citizens committed to collective well-being.